2022
DOI: 10.1007/s00392-022-02138-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of right ventricular function after intermediate-risk pulmonary embolism: results from the multicentre Pulmonary Embolism International Trial (PEITHO)-2

Abstract: Background Right ventricular (RV) function plays a critical role in the pathophysiology and acute prognosis of pulmonary embolism (PE). We analyzed the temporal changes of RV function in the cohort of a prospective multicentre study investigating if an early switch to oral anticoagulation in patients with intermediate-risk PE is effective and safe. Methods Echocardiographic and laboratory examinations were performed at baseline (PE diagnosis), 6 days and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…ASL FS et al also showed that none of the patients with haemodynamic instability or reperfusion therapy were diagnosed with CTEPH during follow-up [17]. However, in patients with haemodynamically stable pulmonary embolism, there was no signi cant difference in treatment method between the groups (p > 0.05), which was consistent with the conclusions reached in previous studies [22] and may be related to less thrombolytic therapy in patients with stable haemodynamics. In the present study, the application of catheter-directed thrombolysis (CDT) in patients with intermediate-high risk pulmonary embolism was conducive to the recovery of right heart function and pulmonary artery pressure and to reducing CTEPH incidence [23,24].…”
Section: Discussionsupporting
confidence: 74%
“…ASL FS et al also showed that none of the patients with haemodynamic instability or reperfusion therapy were diagnosed with CTEPH during follow-up [17]. However, in patients with haemodynamically stable pulmonary embolism, there was no signi cant difference in treatment method between the groups (p > 0.05), which was consistent with the conclusions reached in previous studies [22] and may be related to less thrombolytic therapy in patients with stable haemodynamics. In the present study, the application of catheter-directed thrombolysis (CDT) in patients with intermediate-high risk pulmonary embolism was conducive to the recovery of right heart function and pulmonary artery pressure and to reducing CTEPH incidence [23,24].…”
Section: Discussionsupporting
confidence: 74%
“…This signal for preservation of RV function is subject to bias by unmeasured confounders, but may have clinical signi cance given that persistent RV dysfunction predicts poorer long-term clinical outcomes for patietns with acute pulmonary embolism. 52 Propensity-matched analyses demonstrated greater adherence to guideline-recommended follow-up metrics including referral to and achievement of dedicated PE follow-up and consideration of anticoagulation. This increased surveillance may also account for the observed trend toward an increase in documented PE/VTE recurrence among PCs, who tended to undergo more imaging studies, and had greater contact with the healthcare system.…”
Section: Discussionmentioning
confidence: 98%